Reality and Measures for Developing Integrated Teaching Capacity for High School Chemistry Teachers - Thi Thu Hoai, Vu (VNU Journal of Science: Education Research; Vol 36 No 2DO - 10.25073/2588-1159/vnuer.4403, 2020)
Integrated teaching competence is one of the most important competencies teachers capacity adapting to the requirements of reforming the general education curriculum. Researching and application of an integrated teaching perspective has been interested by many educators and teachers to research and apply in teaching practice. However, the reality of the teaching practice of teachers in general and teachers of chemistry in high schools is needed to concern. This paper researches the capacity teaching at high schools and proposes the measures to develop this capacity for teachers and chemistry teacher students in order to contribute to improving the teaching capacity of teachers, meeting the requirements of a new school education program.